1967
DOI: 10.1002/jhet.5570040219
|View full text |Cite
|
Sign up to set email alerts
|

Structural modification studies of 3‐piperonylsydnone I. synthesis of piperonyl‐substituted pyrazoles, isoxazoles, triazoles, oxadiazoles and thiadiazoles

Abstract: As a structural modification study of the antimalarial compound 3‐piperonylsydnone, a number of pyrazoles, isoxazoles, 1,2,4‐triazoles, ψ‐1,2,4‐triazoles, 1,3,4‐oxadiazoles, 1,3,4‐thiadiazoles and their intermediates all of which contain the piperonyl moiety have been synthesized. The antimalarial activity of these compounds was found to be less than that of the original sydnone. With the exception of 2,4‐diamino‐5‐piperonylpyrimidine, among the compounds tested, those which showed survival time of eleven days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It was found that the N-N bond is essential for the antiplasmodial activity either in the sydnone or in the piperonyl moiety as highlighted in structures LIV-LVII. However, 3-piperonylsydnone was still the most active molecule among all tested compounds [81]. On the other hand, 4,4-bis (acetamidophenyl) sulfone derivatives were very potent antimalarial agents, while sydnone rendered it less active or inactive when they were combined in one structure LVIII [82].…”
Section: Antimalarial Activitymentioning
confidence: 90%
“…It was found that the N-N bond is essential for the antiplasmodial activity either in the sydnone or in the piperonyl moiety as highlighted in structures LIV-LVII. However, 3-piperonylsydnone was still the most active molecule among all tested compounds [81]. On the other hand, 4,4-bis (acetamidophenyl) sulfone derivatives were very potent antimalarial agents, while sydnone rendered it less active or inactive when they were combined in one structure LVIII [82].…”
Section: Antimalarial Activitymentioning
confidence: 90%